Effect of Social Media Marketing “Instagram” Towards Purchase Intention : Evidence From Plant-Based Milk Product “Oatside” in Indonesia - Whisnu Febriansyah; Ratna Mega Yunita; Reza Nugraha (Eduvest - Journal of Universal Studies, 2024)
In the ever-evolving field of marketing, building and maintaining purchase intent remains a central theme and a significant challenge for marketers. Among various strategies em-ployed to sustain customer brand loyalty, social media marketing has emerged as a recent and effective tool. This study delves into the impact of social media marketing on the pur-chase intent of consumers, an area that is garnering growing interest from both marketing scholars and industry practitioners. The research specifically encompasses customers in Indonesia who follow "Oatside" on Instagram. Oatside is a popular plant-based milk prod-uct, and its Instagram followers form the target demographic for this study. A structured questionnaire was administered to a sample of 130 respondents, serving as the primary data collection method. The collected data were then examined using linear regression analysis conducted via SPSS. The results of the study indicate a positive correlation be-tween purchase intent and several key factors related to the brand's social media pres-ence. These include the brand's provision of entertaining content, facilitation of two-way communication with consumers, presentation of trending topics, and offering of personal-ized content. Each of these elements contributes to enhancing consumer engagement and influencing purchase decisions. As a pioneer in this novel area of marketing, the study not only contributes to the academic understanding of the impact of social media marketing but also suggests practical tactics for industry practitioners. These strategies can be in-strumental in optimizing their social media marketing efforts, thereby enhancing customer engagement and driving purchase intent.